2003
DOI: 10.1097/01.jom.0000079083.95532.b5
|View full text |Cite
|
Sign up to set email alerts
|

Lead Exposure in Radiator Repair Workers: A Survey of Washington State Radiator Repair Shops and Review of Occupational Lead Exposure Registry Data

Abstract: Radiator repair workers in Washington State have the greatest number of very elevated (> or =60 microg/dL) blood lead levels of any other worker population. The goals of this study were to determine the number of radiator repair workers potentially exposed to lead; estimate the extent of blood lead data underreporting to the Occupational Lead Exposure Registry; describe current safety and health practices in radiator repair shops; and determine appropriate intervention strategies to reduce exposure and increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…There are several surveys showing that people who work in lead-related industries have higher blood lead levels than other people [16][17][18][19] . This is an expected condi- tion.…”
Section: Discussionmentioning
confidence: 99%
“…There are several surveys showing that people who work in lead-related industries have higher blood lead levels than other people [16][17][18][19] . This is an expected condi- tion.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, exposure to lead is considered a public and occupational health issue in the world (3). Lead poisoning is an increasing concern, particularly in developing countries, as a result of rapid urbanization, leaded fuels, and industrial pollutions (2).…”
Section: Introductionmentioning
confidence: 99%
“…Lead is in no way useful in human body and any amount of this element is harmful to our body (3). Known complications of long-term exposure to lead include hypertension, toxicity of kidney nephrons, cardiovascular disorders, hemoglobin disorder, cognitive disorders, memory loss and malignity of stomach, lung, and bladder (5-7).…”
Section: Introductionmentioning
confidence: 99%
“…If medically removed, the worker must have blood lead testing performed at least monthly during the removal period. A limited number of studies confined to a specific industry [Jarrett, 2003;Whittaker, 2003] or state of residence [Tumpowsky et al, 2000;Vork et al, 2001; Anderson and Islam, 2006] have reported the distribution of adult BLLs including cases of BLLs !60 mg/dl. To the best of our knowledge, no study has reported the national distribution of workers with BLLs requiring medical removal, nor the level of adherence to OSHA standards once medical removal criteria are met.…”
mentioning
confidence: 99%
“…2000; Vork et al, 2001;Whittaker, 2003;Anderson and Islam, 2006]. Under the Occupational Safety and Health Administration (OSHA) lead standards for General Industry (CFR 1910(CFR .1025 and Construction (CFR 1926.62), if a periodic and a follow-up blood sampling test indicate that the worker's blood lead level (BLL) is !60 mg/dl (or !50 mg/dl for construction), or the average BLL of all tests over a 6-month period (or if there are less than 3 tests over a 6-month period, the average of three consecutive tests) is !50 mg/dl, workers must be removed immediately from further exposure.…”
mentioning
confidence: 99%